Inclusive education in South African further and higher education : reflections on equity, access, and inclusion - Makoelle, Tsediso Michael; Mosito, Cina P. (Emerald Publishing Limited, 2025)
The post-apartheid era saw the South African government introduce a range of policies for building an inclusive education system. Inclusive Education in South African Further and Higher Education provides a historical overview of the evolution of inclusive education, alongside the emergence of concepts such as of equity and access, highlighting how these ideas have evolved, been enacted and practiced in the higher education institutions (HEIs) of South Africa since 2001. Highlighting the barriers encountered in striving for inclusion in higher education in South Africa, chapter authors explore the significance of curriculum for inclusion and unpack the strategies of support and assessment in higher education. The critical aspects of inclusion and exclusion in higher education such as gender, language, technology and leadership are discussed and their impact on access, equity and inclusion is unmasked. Importantly, within this work is the principal and recognition of Indigenous and afro-centric knowledge in this space, how it is recognised and valued, and the manner in which it can be brought to the fore in decolonising the curriculum. Whilst focusing on the South African context, the theoretical and methodological approach adds to the international understanding of access, equity and inclusion in higher education and provides important insights for policymakers, scholars, students and researchers in inclusive education and higher education globally.
Includes index.
Keywords: Education, Higher -- South Africa -- History -- 21st century.; Education -- Inclusive Education.; Higher education, tertiary education.; Educational strategies and policy: inclusion.; elektronické knihy; electronic books